Comparison of biofilm-degrading activities of two glycoside hydrolase family 20 enzymes against clinical and veterinary β-1,6-poly-N-acetyl-D-glucosamine-dependent Staphylococcus aureus isolates - Dabul, Andrei Nicoli Gebieluca [UNESP]; Samaniego, Lorgio Victor Bautista; Cortez, Anelyse Abreu; Scandelau, Samuel Luis; Liberato, Marcelo Vizoná; Kubo, Agatha Ms [UNESP]; Rodrigues, Ana Beatriz [UNESP]; Grotto, Rejane Mt [UNESP]; Valente, Guilherme [UNESP]; Rall, Vera Lúcia Mores [UNESP]; Pratavieira, Sebastião; de Oliveira Neto, Mario [UNESP]; et al. (Elsevier, 2025)
Biofilms shield microbial communities from various environmental threats, including antimicrobial agents. Such protection renders bacterial cells within biofilms more resistant to antimicrobial agents than their planktonic counterparts. Degradation of the exopolysaccharides of the biofilm matrix using glycoside hydrolases (GH) strongly increases the efficacy of antimicrobials against biofilms. Staphylococcus aureus is a leading cause of infections in both humans and animals, with many of its strains producing biofilms rich in β-1,6-N-acetyl-D-glucosamine (PNAG), the primary component of the extracellular matrix of their biofilms. In this study, we recombinantly produced and biochemically characterized two glycoside hydrolases from GH20 family, ApGH20 and ChGH20, both of which specifically target PNAG. These enzymes effectively degraded and inhibited biofilm formation of S. aureus human clinical strain which produces a robust PNAG-based biofilm. Both enzymes also demonstrated high activity against several veterinary S. aureus isolates. All of these isolates have been sequenced and analyzed. Notably, ApGH20 exhibited nearly three orders of magnitude higher activity than ChGH20 in degrading S. aureus biofilm, yet both enzymes similarly enhanced the ability of gentamicin to kill human isolate of S. aureus, albeit at different dosages. These findings further demonstrate that application of glycoside hydrolases, when combined with antimicrobial agents, is a promising strategy for treating infections caused by pathogenic S. aureus strains. STATEMENT OF SIGNIFICANCE: Antimicrobial resistance is a very significant health problem, resulting in millions of deaths worldwide. Pathogenic bacteria become resistant to antibiotics using various mechanists, one of which is to protect themselves by biofilms. Staphylococcus aureus is a leading cause of infections in both humans and animals, with many of its strains relying on β-1,6-N-acetyl-D-glucosamine (PNAG) polysaccharide as an important part of their biofilms. Here we produced two glycoside hydrolase enzymes which specifically target PNAG. We showed that the enzymes effectively degraded and also prevented biofilm formation of S. aureus human clinical and several veterinary isolates. Both enzymes similarly enhanced efficiency of gentamicin against S. aureus, albeit at different dosages, which might hold promise to treat infections caused by these pathogenic bacteria.